2014
DOI: 10.1111/psyp.12399
|View full text |Cite
|
Sign up to set email alerts
|

Right‐lateralized alpha desynchronization during regularity discrimination: Hemispheric specialization or directed spatial attention?

Abstract: When actively classifying abstract patterns according to their regularity, alpha desynchronization (ERD) becomes right lateralized over posterior brain areas. This could reflect temporary enhancement of contralateral visual inputs and specifically a shift of attention to the left, or right hemisphere specialization for regularity discrimination. This study tested these competing hypotheses. Twenty-four participants discriminated between dot patterns containing a reflection or a translation. The direction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 56 publications
3
50
1
Order By: Relevance
“…Sasaki et al 2005). A right hemisphere advantage for symmetry processing has also be found with TMS and occipital alpha desynchronization analysis (Verma et al 2013; Bona et al 2014; Wright et al 2015). …”
Section: Study 1: Discussionmentioning
confidence: 73%
“…Sasaki et al 2005). A right hemisphere advantage for symmetry processing has also be found with TMS and occipital alpha desynchronization analysis (Verma et al 2013; Bona et al 2014; Wright et al 2015). …”
Section: Study 1: Discussionmentioning
confidence: 73%
“…Wright et al [57] have recently tested this idea. Participants were presented with vertical or horizontally oriented patterns ( Figure 5A), and made a reflection vs. translation judgement.…”
Section: Question Five: How Are Brain Rhythms In the Two Hemispheres mentioning
confidence: 99%
“…Wright et al [57] compared the SPN with horizontal and vertical orientations. For horizontal patterns the paired elements are presented within the same hemifield, but the SPN was similar irrespective of orientation.…”
Section: Question One: Is There An Automatic and Sustained Response Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In a following fMRI study, Wilkinson and Halligan [29] found that the cerebral substrate of the LVF advantage for detecting the presence/absence of symmetry in lines is the right anterior cingulate gyrus. Bertamini and Makin [30] found that symmetry processing induced occipital alpha Event Related Desynchronization (ERD) in the right hemisphere, confirming at the electrophysiological level the stronger right-than left-hemispheric involvement in symmetry detection (see also [31,32]). In another electroencephalographic (EEG) study, Makin and colleagues [33] also showed that the Sustained Posterior Negativity is stronger for reflection than for rotation and translation, and that this is true when participants were explicitly required to detect the presence of regularity in the stimuli.…”
Section: Introductionmentioning
confidence: 81%